Do social and environmental screens influence ethical portfolio performance? Evidence from Europe - Eduardo Ortas; José M. Moneva; José M. Moneva (BRQ Business Research Quarterly, 2014)
This work aims to test whether social and environmental screening processes could determine the financial performance of ethical or Socially Responsible Investment (SRI) strategies in the European context. We compare the risk-adjusted returns and systematic risk levels obtained by the two mainstream SRI equity indexes in Europe with those achieved by their official benchmarks. We find that, although these SRI indexes do not underperform their benchmarks in terms of risk-adjusted returns, they experience higher levels of risk. Additionally, the results show that higher screening intensity results in higher risk for the SRI indexes. Furthermore, the underperformance in terms of risk associated with the SRI indexes is worse in periods when there is a market downturn. This may indicate that SRI indexes are more sensitive to changes in the market cycle, because SRI indexes include companies that are more affected by market fluctuations."
Keywords: 650; Corporate social responsibility; Socially responsible investment; State-space models; Risk management